2016
DOI: 10.1177/1045389x15610912
|View full text |Cite
|
Sign up to set email alerts
|

Healing of shape memory polyurethane fiber-reinforced syntactic foam subjected to tensile stress

Abstract: In this study, healing of conventional non-shape memory syntactic foam embedded with shape memory polyurethane fibers was investigated per the biomimetic close-then-heal strategy. The syntactic foam was made of epoxy matrix dispersed with 30% by volume of glass microballoons, 5% by volume of shape memory polyurethane fibers, and three levels of thermoplastic healing agent (5%, 10%, and 15% by volume). Notched beam specimens were prepared and fractured by tension to create macroscopic cracks. Three levels of te… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
10
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 30 publications
(10 citation statements)
references
References 54 publications
0
10
0
Order By: Relevance
“…Among SMPs, polyurethane (PU) and its nanocomposites were studied by many researchers (Cai et al, 2013; Gu et al, 2016; Zhang et al, 2015). Thermoplastic polyurethane (TPU), as a popular SMP material, is shown to be a suitable material for medical equipment because of its flexibility, durability, and biological stability (Simmons et al, 2006).…”
Section: Introductionmentioning
confidence: 99%
“…Among SMPs, polyurethane (PU) and its nanocomposites were studied by many researchers (Cai et al, 2013; Gu et al, 2016; Zhang et al, 2015). Thermoplastic polyurethane (TPU), as a popular SMP material, is shown to be a suitable material for medical equipment because of its flexibility, durability, and biological stability (Simmons et al, 2006).…”
Section: Introductionmentioning
confidence: 99%
“…After that, the molten thermoplastic resin particles flowed to complete the crack filling and repair. Moreover, Zhang et al [109] further introduced SMPFs into foam and other structures to achieve the self-healing function of fiber reinforced composites.…”
Section: Self-healingmentioning
confidence: 99%
“…Based on previous studies, it is found that both the recovery strain and recovery stress of the tension‐programmed SMP fibers play a key role in closing cracks 20 . In particular, a certain recovery stress is needed to overcome the constraint by materials surrounding the crack or even by external tensile load in order to bring the fractured surfaces in contact 12,16,21 . While shape memory polymers usually have large recovery strain, their recovery stress is limited 22 .…”
Section: Introductionmentioning
confidence: 99%